Optical Bistability Effect of Two-port Nonlinear Fiber Mach-Zehnder Interferometer - Quy, Ho Quang; Sau, Vu Ngoc; Hoa, Nguyen Van; Tam, Nguyen Thi Thanh (Communications in Physics, 2011)
In this article, the dependence of bistability characteristic of the two-port nonlinear fiber Mach-Zehnder interferometer (TPNFMZI) on initial phase shift, wavelength of input signal, nonlinear coefficient of refractive index and length of nonlinear fiber is investigated and discussed. The results of this work play an important role in designing the TPNFMZI and its application in the future.